The late endocytic Rab39a GTPase regulates the interaction between multivesicular bodies and chlamydial inclusions. - Gambarte Tudela, Julian Alberto (2015)
Given their obligate intracellular lifestyle, Chlamydia trachomatis ensure their access to multiple host sources of essential lipids by interfering vesicular transport. These bacteria hijack Rab6-, Rab11- and Rab14-controlled trafficking pathways to acquire sphingomyelin from the Golgi apparatus. Another important source of sphingolipids, phospholipids and cholesterol are multivesicular bodies (MVBs). Despite their participation in chlamydial inclusion development and bacterial replication, the molecular mechanisms mediating MVBs-inclusion interaction remain unknown. In the present study, we demonstrate that Rab39a labels a subset of late endocytic vesicles -mainly MVBs- that move along microtubules. Moreover, Rab39a is actively recruited to chlamydial inclusions throughout the pathogen life cycle by a bacterial-driven process and depending on its GTP/GDP binding state. Interestingly, Rab39a participates in the delivery of MVB and host sphingolipids to maturing chlamydial inclusions thereby promoting inclusion growth and bacterial development. Altogether, our findings indicate that Rab39a favours chlamydial replication and infectivity. This is the first report showing a late endocytic Rab GTPase involved in chlamydial infection development.